Blocking of Inactive Accounts by PPATK from the Perspective of Sharia Economic Law and Civil Law: Analysis of Property Rights Protection and Justice - Rita Defriza; Ardina Khoirun Nisa (FOUNDAE (Foundation of Advanced Education), 2026)
The freezing of inactive bank accounts by Indonesia's Financial Transaction Reports and Analysis Center (Pusat Pelaporan dan Analisis Transaksi Keuangan, PPATK), the country's Financial Intelligence Unit (FIU), has generated significant legal debate due to the tension between preventive anti-money laundering measures and the protection of individual property rights. However, little attention has been paid to how Civil Law and Sharia Economic Law can be harmonized to assess the legitimacy and justice of account-freezing policies. This study aims to analyze the legal mechanism governing PPATK's account-freezing authority and evaluate its implications for the protection of property rights from the perspectives of Civil Law and Sharia Economic Law. Using a normative juridical approach, the study examines Indonesia's Anti-Money Laundering Law, the Indonesian Civil Code, and classical Islamic jurisprudential sources through statutory, conceptual, and comparative legal analyses. The findings reveal two complementary dimensions of legal protection. From the perspective of Civil Law, account freezing constitutes a legitimate preventive administrative measure only when it is implemented within a clear legal framework, supported by due process, transparent procedures, and reasonable time limitations that prevent disproportionate interference with ownership rights. From the perspective of Sharia Economic Law, the policy is justified by the principles of maslahah (public interest) and la darar wa la dirar (the prohibition of harm), as it seeks to preserve the integrity of the financial system while protecting lawful ownership from illicit financial activities. The analysis further demonstrates that substantive justice can be realized only when preventive state authority is exercised transparently, proportionately, and with effective legal remedies that enable account holders to recover legitimate access to their assets. This study contributes to the development of legal scholarship by proposing a proportionality-based framework that harmonizes Civil Law and Sharia Economic Law in balancing financial security objectives with the protection of individual property rights. The proposed framework extends existing legal discourse by offering a normative model for strengthening legal certainty, accountability, and substantive justice in Indonesia's financial regulatory system.